ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI APLIKASI PENCATATAN KEUANGAN - Andriani, Juwita; Nur Arifah, Amalina; Eka Setyaputri, Khairina (Universitas Lancang Kuning, 2023)
Financial management in a well-planned and well-planned way is very useful to help create more focused life goals, and make quick decisions. One of the causes of people's inefficiency in managing their finances is the high level of activity among the people, moreover managing finances manually takes too long to make decisions. Financial management is important for some people, considering that financial problems are a very sensitive issue for today's life, the culture among the people, especially in urban areas, is that the majority have a consumptive lifestyle. The importance of financial management is still a lot of people who are not aware of it, especially for personal financial management. The population in this study were all users of financial recording applications (financial records). The samples in this study were students, lecturers, civil servants, BUMN employees, private employees and others who are in the Special Region of Yogyakarta. This study used a purposive sampling technique. The purposive sampling technique is a data collection technique with certain considerations or criteria, in this study the criteria are only users who use financial recording applications (financial records). The results in this study are Self-efficacy has a positive effect on perceived ease of use, Perceived ease of use able to mediate Self-efficacy on intentions to use financial recording applications, Subjective norms have a positive effect on perceived usefulness, Perceived usefulness is able to mediate Subjective norms on intentions to use financial recording applications, Perception Ease of use has a positive effect on the intention to use the financial recording application, perceived usefulness has a positive effect on the intention to use the financial recording application. Keyword: Self-efficacy, perceived ease of use, Subjective norm, perceived usefulness, intention to use the financial recording application.